Investigation of effect of viscosity on crystallization ability of spodumene glass-ceramic materials - Savvova, O.; Babich, O.; Shadrina, G.; Kuriakin, M.; Grivtsova, A. (Functional Materials, 2016)
The influence of viscosity on crystallization ability, which determines strength properties of protective spodumene glass-ceramic materials, has been studied. It has been established that formation of volume-crystallized structure in lithium-aluminosilicate glasses in conditions of two-stage thermal treatment in the viscosity range of 109 Paps allows provision of mechanical properties required to obtain resistance against the action of energy-destructive factors. Obtained results may be used in developing glass-ceramic materials for modern composite armor.